2020
DOI: 10.1038/s41375-020-0910-1
|View full text |Cite
|
Sign up to set email alerts
|

Hematological features of persons with COVID-19

Abstract: We studied admission and dynamic demographic, hematological and biochemical co-variates in 1449 hospitalized subjects with coronavirus infectious disease-2019 (COVID-19) in five hospitals in Wuhan, Hubei province, China. We identified two admission co-variates: age (Odds Ratio [OR] = 1.18, 95% Confidence Interval [CI] [1.02, 1.36]; P = 0.026) and baseline D-dimer (OR = 3.18 [1.48, 6.82]; P = 0.003) correlated with an increased risk of death in persons with COVID-19. We also found dynamic changes in four co-va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
118
1
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(137 citation statements)
references
References 33 publications
12
118
1
6
Order By: Relevance
“…A meta-analysis of 7,613 COVID-19 patients revealed that patients with severe disease had a lower platelet count than those with non-severe disease. Additionally, the non-survivors had a much lower platelet count than the survivors [ 25 , 36 ]. However, not all studies have found platelet counts to be a predictor of COVID-19 mortality [ 37 ].…”
Section: Plateletsmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis of 7,613 COVID-19 patients revealed that patients with severe disease had a lower platelet count than those with non-severe disease. Additionally, the non-survivors had a much lower platelet count than the survivors [ 25 , 36 ]. However, not all studies have found platelet counts to be a predictor of COVID-19 mortality [ 37 ].…”
Section: Plateletsmentioning
confidence: 99%
“…Temporally increasing D-dimer levels indicate the progressive severity of COVID-19 infection and can be used as a predictor that more aggressive critical care will be needed. Of nearly 1,500 COVID-19 hospital admissions, Li et al [ 25 ]found two admission covariates that correlated with an increased risk of death: age (OR 1.18; 95% CI 1.02–1.36) and baseline D-dimer level (OR 3.18; 95% CI 1.48–6.82).…”
Section: Coagulationmentioning
confidence: 99%
See 1 more Smart Citation
“…A crucial clinical aspect of the COVID-19 outbreak is the possible outcomes of the disease. The severity spectrum of COVID-19 varies from mild asymptomatic to severe and critical conditions [3]. Critical patients will need timely intensive care unit (ICU) admission and ventilators.…”
Section: Read Full License Introductionmentioning
confidence: 99%
“…The issue of lymphocytopenia is especially important because it may correlate with survival. In a study of 1,571 subjects with COVID-19 we found a significant difference between 1,440 survivors (median 1.2 × 10E+9/L [IQR 0.9, 1.7 × 10E+9/L]) and 131 subjects who died (0.5 × 10E+9/L [0.4, 0.8 × 10E+9/L]; p < 0.001) [ 2 ]. Another example are data on admission prothrombin time.…”
mentioning
confidence: 99%